Statements by unidentified authors regarding an ambush by B. Company, 8th Battalion, on 27 July 1920, and activities in England in 1921 on release from Birmingham Prison
First statement annotated by Florence O'Donoghue and others. Second statement makes reference to O'Donoghue, death of Tadg Sullivan and search for "Monkey" McDonnell.
Keywords: O'Brien, Art Patrick, -- 1872-1949; McDonnell, Daniel; Thornton, Frank, -- 1891-1965; Irish Republican Army; Ireland -- History -- War of Independence, 1919-1921